The Role of the Anesthesiologist during Magnetic Resonance-Guided Focused Ultrasound Thalamotomy for Tremor: A Single-Center Experience - Alon Sinai; Yeshayahu Katz; Menashe Zaaroor; Olga Sandler; Ilana Schlesinger (Parkinson's Disease)
Ablative incisionless neurosurgery has become possible through advances in focused ultrasound and magnetic resonance imaging (MRI). The great advantage of MRI-guided focused ultrasound (MRgFUS) is that the ablation is performed through an intact skull without surgery. Here, we review the new modality of MRgFUS for treating tremor and enlighten the role of the anesthesiologist in the unique procedural setting of the MRI suite. During the MRgFUS process, the patients should be awake and are required to cooperate with the medical staff to allow assessment of tremor reduction and potential occurrence of adverse effects. In addition, the patient’s head is immobilized inside the MRI tunnel for hours. This combination presents major challenges for the attending anesthesiologist, who is required to try to prevent pain and nausea and when present, to treat these symptoms. Anxiety, vertigo, and vomiting may occur during treatment and require urgent treatment. Here, we review the literature available on anesthetic management during the procedure and our own experience and provide recommendations based on our collected knowledge.